Effect of environmental gradients on diversity and plant community distribution in remnant dry Afromontane forest of Mount Duro, Nagelle Arsi, Ethiopia - Teshome, Mengistu; Asfaw, Zebene; Dalle, Gemedo (Biodiversity: Research and Conservation, 2020)
For forest ecosystem management to be effective, explicit understanding of the species diversity-environmental relationship along elevation gradient is crucial. This study aimed at identifying and describing plant communities and also documenting their species diversity. Evaluation of relationships between selected environmental variables and species diversity was another objective of this study. Systematic sampling techniques were used to collect vegetation data in a total of forty two sample plots (size=20×20 m). Within main plots, four sub-plots of 5×5 m were established at four corners and – one sub-plot of the same size in the center. These plots were used for shrub and herb diversity assessment. Within each sample plot, all plant species were documented and their scientific names were identified. Environmental variables, such as: elevation, aspect and slope, were also recorded for each main plot. Species diversity was determined using Shannon-Wiener diversity index and evenness in R statistical software. Agglomerative hierarchical clustering method was used for plant community classification. The total of 44 plant species belonging to 30 families was documented. Four plant community types were identified with different diversity, evenness and species richness. These plant communities were: Afrocurpus falcatus-Ficus sur, Maesa lanceolata-Bersama abyssinica, Vernonia myriantha-Urera hypselodendron and Croton machrostachus-Tecleanobilis occurring at average elevation of 2521, 2429, 2329, and 2364 m asl, respectively. Maesa lanceolata-Bersama abyssinica community type exhibited the highest species diversity and evenness followed by Croton machrostachus-Teclea nobilis community type showing the fact that median elevation ranges were rich in species. Elevation and slope gradient explained significant variation in species richness in the studied forest. For effective conservation of biodiversity and sustainable management of the forest ecosystem, further research on the impacts of anthropogenic disturbances and soil properties is recommended as a result of this study.